The context and approaches of biodiversity conservation : a debate of its impacts on poverty alleviation in communities close to Skukuza Game Reserve, South Africa - Mnisi, P. T. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
Biodiversity conservation is linked with poverty alleviation globally. It is believed to be paramount in terms of creating employment opportunities, producing revenue, creation of small businesses and entrepreneurial prospects to help in terms of escaping poverty. Alleviating poverty has mostly been a main goal to be achieved by several countries. Numerous researchers contended that biodiversity conservation could assist in accomplishing the process of poverty alleviation. Biodiversity conservation was perceived into an economic channel for poverty alleviation in South Africa. In 1994, after government of South Africa gained its democratic dispensation, laws and policies such as the Constitution of South Africa of 1996, the White Paper on the Conservation and the National Environmental Management: Biodiversity Act of 2004 were presented on paper to promote participation of communities in matters concerning conservation. However, none of the acts introduced were brought into practice and communities continued to be left out during decision-making processes. Therefore, the purpose of this theoretical paper is to extensively discuss the context and approaches of biodiversity conservation and debating its impacts on poverty alleviation in communities close to Skukuza Game Reserve in South Africa. The literature-based methodology approach was used from which data was extracted from private documents, scholarly articles, newspaper articles and government publications. The theoretical paper found that the challenging debate between biodiversity conservation and poverty alleviation is still far from reaching a balanced solution. The economy of the country is not flourishing. That is because poverty unemployment and inequity remain the tripartite of South Africa. The Gross Domestic Product (GDP) does not factor biodiversity into the equation. As a result, a balance between biodiversity conservation and poverty alleviation should be created. Considering the above discussion, the paper concludes that the conservation of biodiversity negatively affects the process of poverty alleviation and simultaneously works as a strategy for achieving poverty alleviation only if the negative impacts have been ameliorated.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Biodiversity conservation; Poverty alleviation; Community development; Environmental sustainability; South Africa; Biodiversity conservation -- South Africa -- Mpumalanga; Community development -- South Africa -- Mpumalanga; Sustainable development -- South Africa -- Mpumalanga